CUSTODIAL TORTURE IN POLICE STATIONS: CAUSES AND AREAS OF IMPROVEMENT (NATIONAL CAPITAL LAW JOURNAL, 2000)
NA
Keywords: Custodial Torture; Police Custody Deaths; Third Degree Methods; Criminalisation Of Politic; Police Reform; Investigative Stress; Organisational Pressure; Judicial Delay; Human Rights Violation; Criminal Justice System Coordination